Electron-doping-enhanced trion formation in monolayer molybdenum disulfide functionalized with cesium carbonate - Lin, Jia Dan (2014)
We report effective and stable electron doping of monolayer molybdenum disulfide (MoS2) by cesium carbonate (Cs2CO3) surface functionalization. The electron charge carrier concentration in exfoliated monolayer MoS2 can be increased by about 9 times after Cs2CO3 functionalization. The n-type doping effect was evaluated by in situ transport measurements of MoS2 field-effect transistors (FETs) and further corroborated by in situ ultraviolet photoelectron spectroscopy, X-ray photoelectron spectroscopy, and Raman scattering measurements. The electron doping enhances the formation of negative trions (i.e., a quasiparticle comprising two electrons and one hole) in monolayer MoS2 under light irradiation and significantly reduces the charge recombination of photoexcited electron–hole pairs. This results in large photoluminescence suppression and an obvious photocurrent enhancement in monolayer MoS2 FETs.